ARSIP FOTO UNIVERSITAS DIPONEGORO SEBAGAI MEMORI KORPORAT: LANDASAN DIGITALISASI ARSIP FOTO - Handayani, Tri; Taufiq Kurniawan, Amin (Faculty of Humanities, Diponegoro University, 2014)
Abstract This paper discusses about digitalization of Diponegoro University’ courtesy photo archives. These efforts done through transferring conventional photo to electronic media, and then to perform it on website. Finally, as concluding remark that photo archives management base on website become quicker and easier of archives retrival possible. Keywords: digitalization of photo archives, corporate memory, Diponegoro University